Electronic Commerce - Turban, Efraim; King, David; Lee, Jae Kyu; Liang, Ting-Peng; Turban, Deborrah C. (Springer, 2015)
There has been a severe recession in the world economy in recent years, yet electronic commerce, the topic of this book, has grown rapidly, with companies like Facebook, Google, Pinterest, Alibaba Group and Amazon.com setting new levels of performance every year. Electronic commerce (EC) is a business model in which transactions take place over electronic networks, mostly the Internet. It includes the process of electronically buying and selling goods, services, and information. Certain EC applications, such as buying and selling stocks and airline tickets online, are reaching maturity, some even exceeding non-Internet trade volumes. However, EC is not just about buying and selling; it also is about electronically communicating, collaborating, and discovering information. It is about e-learning, customer service, e-government, social networks, and much more. EC is having an impact on a signifi cant portion of the world, affecting businesses, professions, trade, and of course, people. The most important developments in EC since 2012 are the phenomenal growth of social networks, especially Facebook, Google+, and Twitter, and the trend toward conducting EC via mobile devices. Other major developments are the global expansion of EC, especially in China, where you can fi nd the world’s largest EC company. In addition, some emerging EC business models are changing industries (e.g., travel, banking, fashion, and transportation). In the 8th edition, we bring forth the latest trends in e-commerce, including social businesses, social networking, social collaboration, innovations, and mobility. Note: Portions of this book were previously published by: Pearson Education, Inc. under the title: Electronic Commerce 2012: A Managerial and Social Networks Perspective.
A Managerial and Social Networks Perspective